Pengaruh Pengetahuan, Kesadaran, dan Pemanfaatan Teknologi Informasi terhadap Kepatuhan Wajib Pajak Orang Pribadi - Nadila Meilia Nurrohmah; Fadjar Harimurti (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to determine the influence of knowledge, awareness, and utilization of information technology on individual taxpayer compliance in KP2KP Sragen. The hypothesis of this study is that knowledge, awareness, and utilization of information technology have a positive effect on individual taxpayer compliance. This study uses a survey method conducted on individual taxpayers in Sragen Regency. This type of research uses quantitative data used in this study from the results of questionnaire data which are then processed using the SPSS application. The data source is primary data. The sampling technique in this study uses the convenience sampling method with 100 taxpayers as respondents. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that the results of the X1 t-test are negative and not proven true. The X2 t-test has a significant positive effect and is proven true. X3 has a significant negative effect and is not proven true. The F test shows a significant influence simultaneously. The results of the coefficient of determination mean that the contribution of the influence of the independent variable is 25.7% while the remaining 74.3% is explained by other variables besides the independent variables studied by the author, for example Tax Sanctions, Taxpayer Income, Tax Socialization, and Patriotism